Wave-current interaction with three-dimensional bodies in a channel. (1st April 2022) - Huang, J.; Teng, B.; Cong, P.W.
Abstract: A frequency-domain numerical model is developed to investigate the hydrodynamic properties of three-dimensional bodies of arbitrary geometry subjected to the action of waves and weak current in a channel based on higher order boundary element method. The problem is divided into a steady problem and an unsteady problem to be solved separately, where the unsteady potentials are given by two sets of integral equations based on linearizing the channel Green function and the velocity potential with the normalized current speed. The first-order wave force is obtained by the pressure integration over the body surface and the second-order drift force is evaluated by the far-field analysis. After examining the validation of the numerical model with some generalized relations derived in the present study, numerical studies for a Lewis-form ship and a four-column structure are performed to investigate the influence of channel walls on the hydrodynamic properties of bodies. Numerical results show that compared with the open-sea results, the side-wall effects become obvious when the oscillating frequencies are close to the transverse resonant frequencies of the channel, and compared with the cases without current, the current effects may enhance the interaction between the body and the reflected waves from the channel walls. Highlights: The hydrodynamics of three-dimensional bodies subjected to the action of waves and current in a channel is investigated. The effective boundary integral equations for the steady and unsteady potentials are derived. Compared with the cases without current, the current may enhance interference between the body and reflected waves.